2013
DOI: 10.1037/a0028816
|View full text |Cite
|
Sign up to set email alerts
|

The hue of shapes.

Abstract: This article presents an experimental study on the naturally biased association between shape and color. For each basic geometric shape studied, participants were asked to indicate the color perceived as most closely related to it, choosing from the Natural Color System Hue Circle. Results show that the choices of color for each shape were not random, that is, participants systematically established an association between shapes and colors when explicitly asked to choose the color that, in their view, without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
117
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(132 citation statements)
references
References 28 publications
(41 reference statements)
15
117
0
Order By: Relevance
“…In other words, round shapes tend to be associated with heavy colors, and sharp shapes tend to be matched with light colors. These results partially supported Albertazzi et al (2013), in which color "warmth" ac counted for the FI factor, and "lightness" explained the F2 factor. However, in our preliminary experiment, we also tested the "light/ dark" ratings of colors and shapes, but we did not observe any congruent correlations with color and shape contributions to the FI or F2 factors.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…In other words, round shapes tend to be associated with heavy colors, and sharp shapes tend to be matched with light colors. These results partially supported Albertazzi et al (2013), in which color "warmth" ac counted for the FI factor, and "lightness" explained the F2 factor. However, in our preliminary experiment, we also tested the "light/ dark" ratings of colors and shapes, but we did not observe any congruent correlations with color and shape contributions to the FI or F2 factors.…”
Section: Resultssupporting
confidence: 75%
“…Color warmth seemed to play a role in the color-shape associations (Albertazzi et al, 2013). Therefore, we examined the consis tency of the color-shape associations according to color warmth.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly to other studies on cross-modal associations with color where brightness emerged as a salient characteristic (e.g., Albertazzi & Da Pos, 2012;Kim, 2013), we have found a strong relationship between brightness and intensity of haptic stimuli across all haptic sensations. The most intense haptic sensations were associated with the color choices of the lowest brightness.…”
Section: Discussionmentioning
confidence: 52%
“…Another reason for eliminating this characteristic is that Ludwig and Simner viewed pointiness/roundness as one property with pointy on one side of the continuum and round on the other side; it is, however, unclear whether we actually perceive pointy/round as a property rather than independent shape characteristic, and whether we actually perceive a sphere, for example, to be on the other side to a triangle on the continuum. This is a particularly problematic issue considering that visual shapes are systematically associated with information from other modalities (e.g., Albertazzi & Da Pos, 2012;Spector & Maurer, 2011). Taking into account the evidence that tactile and visual shape processing converge in the lateral occipital complex (Amedi et al, 2002), one might also consider the possibility of the spillover of visual shape and color associations to tactile shape and color association.…”
mentioning
confidence: 99%
“…However, alternative dimensions could also explain these associations. For example, Albertazzi et al (2013) reported on a compatibility effect between specific hues and shapes. In their studies, participants were presented with several shapes (e.g., cone, triangle, square), and were asked to choose a color from a Hue Circle, which they thought was mostly related to the shape.…”
Section: Schietecat Et Al: Part 2 -Dimension-specific Polarity Attribmentioning
confidence: 99%